Rhinocylapoides brachypterus, a new cylapine genus and species from Malaysia (Hemiptera: Heteroptera: Miridae) - Wolski, Andrzej; Gorczyca, Jacek (Zootaxa, 2011)
Rhinocylapoides brachypterus gen. et sp. nov. is described from Malaysia. Illustrations of the male genitalia, color photographs of the adult, and a habitat photograph of specimens of the new genus are provided.